Laboratory animal welfare: environmental enrichment shows positive effect on animal testing - Massari, Catia Helena de Almeida Lima (2019)
Reproductive and developmental toxicology has focused on the need to approach the effects of organism exposure to various drugs during pregnancy after the mid-50’s, when the thalidomide tragedy stroke humanity. In recent decades, this area of study has developed a lot due to animal testing, raising awareness on the need to improve the quality of life of such animals. Therefore, this paper aims to investigate how the science of animal welfare can improve scientific research as a whole, including the reproductive and developmental toxicology fields, by emphasizing environmental enrichment in animal facilities. To do so, we conducted an integrative literature review on several quantitative and qualitative methodological approaches that are applicable to toxicology studies. Here, we present evidence that environmental enrichment improves animal welfare and prevents or reduces the negative effects of captive housing, which must be a principle of toxicological research for ethical, legal and scientific reasons.